2015
DOI: 10.1096/fj.15-270579
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the ubiquitin-specific protease 19 deubiquitinating enzyme protects against muscle wasting

Abstract: The ubiquitin system plays a critical role in muscle wasting. Previous work has focused on the roles of ubiquitination. However, a role for deubiquitination in this process has not been established. Because ubiquitin-specific protease (USP)19 deubiquitinating enzyme is induced in skeletal muscle in many catabolic conditions, we generated USP19 knockout (KO) mice. These mice lost less muscle mass than wild-type (WT) animals in response to glucocorticoids, a common systemic cause of muscle atrophy as well as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…MURF1 is ROS sensitive autophagy related ubiquitin ligase that is greatly increased in atrophying muscles (Bedard et al, 2015; Gomes et al, 2012; Smith et al, 2014; Tanner et al, 2015). ROS, and in sarcopenic muscles from old rats (Alway et al, 2014a; Alway et al, 2015; Hao et al, 2011; Ziaaldini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…MURF1 is ROS sensitive autophagy related ubiquitin ligase that is greatly increased in atrophying muscles (Bedard et al, 2015; Gomes et al, 2012; Smith et al, 2014; Tanner et al, 2015). ROS, and in sarcopenic muscles from old rats (Alway et al, 2014a; Alway et al, 2015; Hao et al, 2011; Ziaaldini et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 may also interact with p62, a protein that plays a role in clearance of protein aggregates, and its inactivation in muscle leads to suppressed autophagy (83). Moreover, knocking out the deubiquitinating enzyme USP19 results in downregulation of autophagy-promoting genes in muscle, indicating that USP19 may promote autophagy (2). A recent report indicates that USP19 can deubiquitinate and stabilize Beclin-1, thereby promoting autophagy (39).…”
Section: The Ups Interacts With Autophagymentioning
confidence: 99%
“…However, it is unlikely that the enhanced physical activity explains all the beneficial metabolic effects observed in the Usp19 −/− mice, as cell autonomous effects of USP19 have also been observed. We have previously shown that silencing Usp19 in skeletal muscle of WT mice leads to protection from muscle wasting due to alterations in protein turnover [14]. In addition, silencing or gene inactivation of Usp19 in muscle cells has been shown to promote their differentiation in vitro [11] or enhance insulin signalling [15], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, USP19 plays an important role in muscle; USP19 regulates myogenic differentiation [11], and female muscle mass through oestrogen receptor-dependent mechanisms [12]. Importantly, Usp19 expression is induced in muscle under catabolic stimuli [13] and the inactivation of the gene in mice is protective against muscle wasting [14,15].…”
Section: Introductionmentioning
confidence: 99%